Resource allocation algorithm for downlink multiuser CoMP system - Yong-hong KUO; Ren-yong WAN; Jian CHEN; Jian WANG (Tongxin xuebao)
For downlink multiuser coordinated multi-point transmission (MU-CoMP) system,a fast resource allocation algorithm was proposed to solve the margin adaptive (MA) problem.Firstly the algorithm estimated the number of sub-carriers for each user based on its average channel gain and minimal-rate requirement,and then an efficient algorithm was designed to complement subcarrier allocation.At last,fast bit-loading was achieved through pre-determining and remov-ing the inefficient spatial subchannels.Simulation results show that the proposed algorithm decreases the total transmit power with both the minimal-rate and bit error rate requirements satisfied,and obtains near-optimal performance with less complexity,compared with the optimal algorithm.